The Death Penalty in Georgia: Still Arbitrary - Ursula Bentele (Washington University Law Quarterly, 1985)
The United States Supreme Court has found death constitutional as a punishment for murder. In Gregg v. Georgia, the Court declared that capital punishment is not, by its very nature, cruel and unusual in violation of the eighth amendment. This Article focuses on the Georgia capital punishment system. The conclusions to be drawn from examination of the Georgia experience have broad application, however, because the Georgia system is typical of modem American capital punishment schemes. If the Georgia statute cannot avoid arbitrary and discriminatory imposition of death sentences, it is difficult to imagine a statute that could effectively perform that task. In Part I, this Article examines the Gregg Court's assumption that safeguards built into the trial and appeal phase of a capital case insure against arbitrary and capricious application of the death penalty in Georgia. The Court in Gregg essentially dismissed the problems inherent in the prosecutor's discretion to charge and the executive's power to grant clemency. The Article will address the issues surrounding those stages in Parts II and III.
Keywords: Capital punishment; Georgia